Phase 1B study of the safety and tolerability of the mineralocorticoid fludrocortisone acetate in patients with geographical atrophy. Issue 1 (1st July 2022) - Hong, Thomas; Chang, Andrew; Maddess, Ted; Provis, Jan; Penfold, Philip
Abstract : Objective: To evaluate the safety and tolerability of a mineralocorticoid, in a single-dose intravitreal (IVT) injection of 1 mg/0.1 mL and 2 mg/0.1 mL fludrocortisone acetate (FCA) in subjects with geographical atrophy (GA) secondary to age-related macular degeneration. Methods and Analysis: This phase 1b study was a two-part dose-escalation prospective study. Part 1 involved a single participant treated with 1 mg/0.1 mL and monitored up to 28 days before being reviewed by a safety review committee. Two subsequent participants were then dosed with the same dose. Part 2 involved a single participant dosed with 2 mg/0.1 mL and monitored up to 28 days when a further five participants were dosed. All participants were followed up for 6 months after baseline. A full ophthalmic assessment was performed at study visits which included GA area, best-corrected visual acuity (BCVA), low-luminance BCVA (LL-BCVA) and intraocular pressure (IOP). Adverse events (AEs) were reported from the first dose of FCA until the end-of-study visit. Results: There were no serious AEs (ocular or systemic) observed with IVT FCA at either 1 mg/0.1 mL or 2 mg/0.1 mL among nine participants. There was no evidence of increased IOP or cataract development. Neither BCVA or LL-BCVA changed significantly in the study-eye over the follow-up period (p=0.28 and 0.38, respectively). Mean GA area increased in the study (0.5 mm 2, p=0.003) and fellow-eyes (0.62 mm 2, p=0.02) over 6 months. Differences between eyes were not significant (p=0.64), and at the lower end of population norms. Conclusion: IVT FCA is clinically safe and well tolerated and did not increase IOP.